Therapeutic Effect Of Warm Fragrant Lemongrass Foot Soak Against Changes In The Joint Pain Scale Of Rheumatoid Arthritis Patients - Syahwal, Muhammad; Aluddin (International Journal of Science, Technology & Management, 2021)
Uric acid is a natural antioxidant produced by the human body, but it can trigger rheumatoid arthritis if the amount exceeds the normal threshold with typical symptoms in the form of pain accompanied by swelling in the joint area, even in advanced conditions there is joint stiffness. Cymbopogon nardus (L.) Rendle or lemongrass is an effective plant to reduce joint pain and swelling. The purpose of this study was to describe the effect of warm lemongrass foot bath therapy on changes in the scale of joint pain in patients with rheumatoid arthritis. This study is a pre-experimental study with one group pre-test and post-test design without a control group, changes after two days of soaking warm lemongrass feet by observing changes in the pain scale of 23 respondents. The Wilcoxon test results showed that there was a change in the pain scale after intervention with a value of p = 0.01, which means that warm scented lemongrass foot soak affects reducing the pain scale of patients with rheumatoid arthritis. The warm sensation of the foot soaking intervention provides a peripheral vasodilation effect which causes a decrease in joint pain in inflamed tissues, the chemical effect of citronellal compounds is around 32-45%, geraniol 12-18%, and citronellol 12-25% in citronella plants are also proven to play a role in reducing pain. This study concluded that warm lemongrass foot soaking therapy affected the changes in the scale of joint pain in Rheumatoid Arthritis.